MMP-1 suppressing activity of high-molecular weight fraction isolated from the roots of Cynanchum wilfordii Hemsley. (January 2018) - Jang, Mi; Cho, Chang-Won; Han, Ah-Ram; Rhee, Young Kyoung; Hong, Hee-Do; Kim, Kyung-Tack; Lee, Sung-Young; Lee, Kwang Min; Jung, Sung Keun; Lim, Tae-Gyu
Highlights: The anti-wrinkle activity of high-molecular weight fraction isolated from Cynanchum wilfordii Hemsley (HMF) was suggested. UVB-suppressed SOD expression was recovered by HMF. HMF directly revealed radical scavenging activity. Abstract: Cynanchum wilfordii Hemsley is a traditional herbal medicine that has been widely used in Asia. In the present study, we investigated the MMP-1 suppressing activity of a high-molecular weight fraction isolated from the roots of C. wilfordii Hemsley (HMF). In human skin tissue, UVB irradiation significantly increased matrix metalloproteinase-1 (MMP-1) expression, while HMF suppressed this effect. The inhibitory effect of HMF was confirmed in both primary human dermal fibroblasts (HDFs) and a human keratinocyte (HaCaT) model. An investigation of the underlying mechanisms responsible revealed that MKK4-JNK, MEK-ERK, and MKK3/6-p38 phosphorylation was downregulated by HMF treatment. HMF also induced a 30–40% increase in DPPH radical scavenging activity and recovered expression levels of the antioxidant enzyme superoxide dismutase. Taken together, these findings suggest that HMF elicits MMP-1 suppressing activity via inhibition of the signaling that drives UVB-induced oxidative stress in human skin.